Relevant aspects to promote innovation in small businesses: Aspectos relevantes para impulsar la innovación en pequeñas empresas - Garcia-Salirrosas, Elizabeth Emperatriz (2020)
Dear Editor,The original article published in your magazine, titled service design for innovation in small andmedium businesses from the author Carvalho (2019) concludes that small companies can innovatetheir services without incurring large costs and demanding a large amount of time, the mostimportant is involved to the users strongly. To complement this research, the study carried out bySánchez, Cervantes, y Peralta (2016) mentions that in order to carry out and efficient managementof the innovation in the small companies, it is necessary to encourage and take advantage of theinnovative skills and abilities of collaborators, involving them during the strategic planning andmotivating them to participate with their ideas in the innovation process. For which, it’s necessaryto create a favorable working environment and formal procedures for the reception and evaluationof the creative ideas that may be presented by the workers. This position is reinforced by the studycarried out by Pertuz, Boscan, Straccia, y Pérez (2016), who recommend developing the capabilitiesof collaborators through the formation of multidisciplinary teams within the organization.